The Constitution as the Foundation of the State Administration of the Republic of Indonesia - Roida Hutabalian (UNISSULA, 2025)
This study explores the 1945 Constitution of the Republic of Indonesia as the fundamental basis for state administration, focusing on its historical evolution, constitutional principles, and the challenges faced in its implementation. Using a qualitative approach through literature study and library research, this research analyzes key amendments made to the Constitution, particularly those introduced during the Reformasi period, which aimed at decentralizing power and enhancing democratic governance. The findings indicate that, even after these reforms, problems such as concentrated executive power, uneven enforcement of the rule of law, corruption, and low levels of political participation continue to persist, obstructing the full fulfillment of constitutional guarantees for justice, equality, and democratic involvement. The study concludes that further institutional reforms, strengthening judicial independence, improving public political literacy, and refining the balance of centralization and regional autonomy are essential for improving the governance system. This research contributes to understanding the practical challenges in implementing Indonesia’s constitutional framework and provides recommendations for future legal and institutional reforms.